2018
DOI: 10.1002/hbm.24073
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high‐field fMRI insights on insight: Neural correlates of the Aha!‐moment

Abstract: Finding creative solutions to difficult problems is a fundamental aspect of human culture and a skill highly needed. However, the exact neural processes underlying creative problem solving remain unclear. Insightful problem solving tasks were shown to be a valid method for investigating one subcomponent of creativity: the Aha!‐moment. Finding insightful solutions during a remote associates task (RAT) was found to elicit specific cortical activity changes. Considering the strong affective components of Aha!‐mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 68 publications
(110 reference statements)
8
103
0
1
Order By: Relevance
“…Other regions, such as the frontostriatal brain circuitries and subcortical dopaminergic network, were also engaged in creativity (Boot, Baas, van Gaal, Cools, & De Dreu, 2017;Tik et al, 2018). Even cerebellum activation, cerebral-cerebellar connectivity, and SMN-DMN connectivity associated with creative thinking have been identified and discussed in previous studies (Saggar et al, 2015;Sun et al, 2019).…”
Section: F I G U R Ementioning
confidence: 89%
See 1 more Smart Citation
“…Other regions, such as the frontostriatal brain circuitries and subcortical dopaminergic network, were also engaged in creativity (Boot, Baas, van Gaal, Cools, & De Dreu, 2017;Tik et al, 2018). Even cerebellum activation, cerebral-cerebellar connectivity, and SMN-DMN connectivity associated with creative thinking have been identified and discussed in previous studies (Saggar et al, 2015;Sun et al, 2019).…”
Section: F I G U R Ementioning
confidence: 89%
“…For example, both in task and resting‐state fMRI studies, the coupling of the DMN and control networks (e.g., FPN), as well as an intermediate switching role of SN, are considered a crucial mechanism of creativity (Beaty, Benedek, Kaufman, & Silvia, ; Beaty et al, , ; Chen et al, ). Other regions, such as the frontostriatal brain circuitries and subcortical dopaminergic network, were also engaged in creativity (Boot, Baas, van Gaal, Cools, & De Dreu, ; Tik et al, ). Even cerebellum activation, cerebral‐cerebellar connectivity, and SMN‐DMN connectivity associated with creative thinking have been identified and discussed in previous studies (Saggar et al, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…in insight problems (see Shen, 2018 for a meta-analysis). Increased activations in the medial temporal lobe (amygdala, hippocampus, and parahippocampal gyrus) (Jung-Beeman et al, 2004;Kizilirmak, Thuerich, Folta-Schoofs, Schott, & Richardson-Klavehn, 2016;Ludmer, Dudai, & Rubin, 2011;Zhao et al, 2013) and right anterior superior temporal gyrus (Jung-Beeman et al, 2004;Tik et al, 2018) amongst other areas have been reported in solutions with compared to without AHA! experience.…”
Section: Neural Basis For the Aha! Experiencementioning
confidence: 99%
“…However, most research investigating the AHA! experience reports brain data at the time of solution or a few seconds before (e.g., Jung-Beeman et al, 2004;Kizilirmak et al, 2016;Luo, Niki, & Phillips, 2004;Tik et al, 2018;Zhao et al, 2013), for the whole trial (Tik et al, 2018) or before the respective trial starts (Kounios et al, 2006;Subramaniam et al, 2009) but not shortly after trial presentation or during the time of search for the solution compound. Only Aziz-Zadeh, Kaplan, and Iacoboni (2009) investigated neural correlates of anagram solutions directly after trial start using fMRI.…”
Section: Neural Basis For the Aha! Experiencementioning
confidence: 99%
“…At the functional level, a recent study on creative problem solving in humans highlights that 452 dlPFC is involved in experiencing a moment of insight 77 . According to this effective connectivity study, 453 dlPFC could upregulate the VTA/SN via striatal connections during such a moment.…”
mentioning
confidence: 99%